The Chinese Public's Perceptions of the European Union: Changes and Stability Revealed by 2010 and 2020 Surveys. - Dong, Lisheng; Woo, Su Yun; Kübler, Daniel (Journal of Contemporary China, 2024)
A survey conducted in 2010 showed that Chinese citizens had rather positive impressions of the EU and were optimistic for the future of China—EU relations. Against the background of increasing tensions between China and the EU, this study focuses on the changes in the Chinese public's perceptions of the EU and of China-EU relations in the last decade. The analysis uses data from the original 2010 survey, as well as from new survey conducted in fall 2020, each including roughly 3000 respondents in six major Chinese cities. Results are that the Chinese public's overall perception of the EU as well as of China-EU relations remains one of general goodwill, even though critical opinions of the EU have become more widespread.